SIFAT PENGERJAAN KAYU SENGON - Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The quality of machining properties of sengon (Paraserianthes falcataria Backer). obtained from 5 years, 10 years, and 15 years old plantation forest in West Java, has been Investigated based on air dried wood moisture content. The results revealed that the average planing quality of wood from 5 years old belong to medium (III). while those at 10 years and 15 years old belong to good (II); the average moulding quality varies from medium (III) to good (II) classes, but turning quality found to be very bad (V); sanding quality is medium (III), while boring quality varies from medium (III) to good (II) classes.